Developing Interactive PowerPoint to Teach Writing Recount Text for the Tenth Graders at SMK Yasmu Manyar - Rizky, Muhammad; Thoyyib Shofi, Ahmad (Lingual Journal of Language and Culture, 2025)
This research focused on the development of interactive PowerPoint as a media to teach writing recount texts for the tenth graders students at SMK Yasmu Manyar. It aimed to provide an appropriate teaching and learning media that was suited to the curriculum used at the school and the need of the English teachers and the students. ADDIE model proposed by Mcgriff (2000) was used as the procedure for developing the product. It consisted of five basic phases which were analysis, design, development, implementation, and evaluation. The subjects of this research were the tenth graders students of Office Management Department 1 and its English teacher. The instruments for collecting data were questionnaire, interview, observation checklist and field note. The data gathered was analyzed using descriptive qualitative method. Based on the result of evaluation, the interactive PowerPoint developed could increase students’ learning interest and help them to learn better. The teacher stated that using the media could make the teaching process easier, presenting the material became more practical and effective. Therefore, it can be concluded that the interactive PowerPoint developed is suitable and appropriate to be used as teaching and learning media at the school to enhance an engaging learning environment in the classroom. The final product is in the application format which has 28 slides and can only be used in an Android device. The size of the application is 16.64 MB.